Benders decomposition for local access network design with two technologies - C. D. Randazzo; H. P. L. Luna; P. Mahey (Discrete Mathematics & Theoretical Computer Science, 2001)
We have worked with the local access network design problem with two cable technologies. This is an optimization problem in graphs that consists of linking an origin node to a set of terminal nodes which have a flow demand. There are also a set of Steiner or transshipment nodes which do not have demand. Each arc of the graph has two associated costs: a variable cost depending on the flow through the arc and a fixed cost associated with the installation of the arc. Moreover, in each arc we can install one of two available technologies: optical fiber or copper (we can also use radio links with any other cable technology). Each one of these technologies has different variable and fixed costs. To be more precise, the fixed cost of the optical fiber is greater than that of the copper, but its variable cost is much smaller. The problem was modeled using a multicommodity flow formulation in which we added some structural constraints. This model was used to apply the Benders decomposition method. The structural constraints have the objective of trying to guarantee that the master problem of the Benders decomposition will yield a tree. The Benders subproblems are trivial network flow problems. The dual variables have commodity meaningfull values and are evaluated in a systematic form. The algorithm was implemented in C++ with CPLEX 3.0 callable library. We have tested the algorithm with some test instances obtained by a generator of problems that we developed.